DESCRIBING THE PHYSICAL, CONTENT, AND LINGUISTIC FEATURES OF GÄDLÄ ABUNÄ THOMAS OF HAYDA - Yirgu, Abinet Asrat; Solomon, Abba Petros (Journal of Oriental Studies, 2025)
This paper examines the physical, content, and linguistic features of the gädl of Abunä Tomas of Hayda, an Ethiopian saint venerated in the Ethiopian Orthodox Tewahǝdo Church. Known by titles such as ’GäbräʾAmǝlak of Šǝre and Saint Abunä Tomas of Hayda, his recognition is primarily limited to the region of Tǝgray. Abunä Tomas was a distinguished disciple of Abunä Täklä Haymanot of Däbrä Libanos and shared a close familial bond with him, underscoring his importance in Ethiopian religious history. The analysis focuses on the Acts of Abunä Tomas, preserved in the monastery of Däbrä Maryam Hayda, located in Šǝre, Tǝgray. The manuscript, uniquely bound in cloth and leather, is attributed to the 19th century based on paleographic analysis. However, the text itself claims its original version (Ur-text) was written by Elsaʾ, a disciple of Abunä Tomas. Compared to other known versions, this manuscript displays more archaic philological characteristics, making it particularly valuable for scholarly study. This article describes the manuscript’s internal and external features, linguistic structure, and technical errors using a descriptive research approach. It highlights the significant role of linguistic elements in contextualizing the manuscript while emphasizing the value of its physical and philological traits. The findings underline the importance of analysing the Acts of Ethiopian saints for a better understanding of their historical and theological significance. Scholars are encouraged to conduct further multidisciplinary research on such manuscripts, incorporating palaeographic, philological, and linguistic analyses to preserve and enhance the appreciation of Ethiopia’s rich religious heritage. Keywords: Gädlä Abunä Thomas, Physical Description, Linguistic Features.